(untitled) (Damascus University Journal for legal sciences, 2026)
International arbitration has an important status among the means of resolving disputes in international contracts. It is resorted to by those dealing in international trade, in order to settle the disputes that result from the commercial transactions. International arbitration contributed to the formation of set of principles and rules that constitute a legal system for arbitration at the world level, that organizes and governs international contract issues, bypassing the stage to resolve international contract. disputes was sought in national legal systems only. Solutions of international transactions, so that they form an original system standing by itself. Among the most important developments in international arbitration contracts is multiparty arbitration, in which there are multiple plaintiffs or defendants, which has become a significant dispute related to international transactions. The multiplicity of parties in international arbitration arose as a result of the need to collect large capital and concentrate on huge projects, which cooperate to achieve the largest possible amount of profits and the least amount of costs and expenses, especially after the tremendous scientific and technical development. This type raises problems related to how the arbitral tribunal is formed, the law applicable to arbitration, how the judgment is issued, cases of its invalidity, and so on, which requires standing on what this type of arbitration is and distinguishing between the true multiplicity of its two original types that occurs because of the arbitration agreement itself or because of the transition and extension of the arbitration agreement and the subsequent one. Resulting from interference and entry into litigation or joining arbitrations and the formal multiplicity of parties to arbitration in international contracts related to the transfer of obligation to a public or private successor, subrogation, or otherwise, given the results that will result from this adaptation.